Can I play, too? - Willems, Mo. (New York Hyperion Books for Children, 2010)
Elephant and Piggie learn to play catch with their new friend Snake.
Ages 4-8.
Accelerated Reader .6.
108263
Keywords: Swine; Elephants; Snakes; Play; Friendship; Pigs; Readers (Primary); Humorous fiction; Children's stories